Recovery from Liver Failure and Fibrosis in a Rat Portacaval Anastomosis Model after Neurointermediate Pituitary Lobectomy - Martín Muñoz-Ortega; Noé Macías-Segura; Javier Ventura-Juárez; Manuel Enrique Ávila-Blanco; Leonardo D. Ponce-Damian; Daniel González-Blas; Esperanza Sánchez-Alemán; Andrés Quintanar-Stephano (Journal of Immunology Research)
Liver diseases, including cirrhosis, viral hepatitis, and hepatocellular carcinoma, account for approximately two million annual deaths worldwide. They place a huge burden on the global healthcare systems, compelling researchers to find effective treatment for liver fibrosis-cirrhosis. Portacaval anastomosis (PCA) is a model of liver damage and fibrosis. Arginine vasopressin (AVP) has been implicated as a proinflammatory-profibrotic hormone. In rats, neurointermediate pituitary lobectomy (NIL) induces a permanent drop (80%) in AVP serum levels. We hypothesized that AVP deficiency (NIL-induced) may decrease liver damage and fibrosis in a rat PCA model. Male Wistar rats were divided into intact control (IC), NIL, PCA, and PCA+NIL groups. Liver function tests, liver gene relative expressions (IL-1, IL-10, TGF-β, COLL-I, MMP-9, and MMP-13), and histopathological assessments were performed. In comparison with those in the IC and PCA groups, bilirubin, protein serum, and liver glycogen levels were restored in the PCA+NIL group. NIL in the PCA animals also decreased the gene expression levels of IL-1 and COLL-I, while increasing those of IL-10, TGF-β, and MMP-13. Histopathology of this group also showed significantly decreased signs of liver damage with lower extent of collagen deposition and fibrosis. Low AVP serum levels were not enough to fully activate the AVP receptors resulting in the decreased activation of cell signaling pathways associated with proinflammatory-profibrotic responses, while activating cell molecular signaling pathways associated with an anti-inflammatory-fibrotic state. Thus, partial reversion of liver damage and fibrosis was observed. The study supports the crucial role of AVP in the inflammatory-fibrotic processes and maintenance of immune competence. The success of the AVP deficiency strategy suggests that blocking AVP receptors may be therapeutically useful to treat inflammatory-fibrotic liver diseases.